Transplanet: A web service dedicated to modeling of planetary ionospheres. (May 2019) - Blelly, P.-L.; Marchaudon, A.; Indurain, M.; Witasse, O.; Amaya, J.; Chide, B.; André, N.; Génot, V.; Goutenoir, A.; Bouchemit, M.
Abstract: We present a new web service (http://transplanet.irap.omp.eu/ ) dedicated to the modeling of planetary ionospheres. Thanks to the development made for IRAP ionospheric model IPIM, it uses a unified description of the different ionized environments (presently Venus, Earth, Mars and Jupiter). The service provides a complete set of parameters characterizing these environments, including the concentration, velocities, temperatures, production rates of the different ions and electron heating rates. It is based on a modular approach allowing for selection of species, date of simulation and location. It is intended to be a support tool to data processing and analysis and we describe how simulation results can be used for such a purpose. The output format has been chosen to ease the interface with external data processing or vizualization tools, including online services. This web service is an open service which aims at providing users with the most relevant and consistent description of the couplings in planetary space environments and it will evolve in a way to increase user control on the simulation through a simplified Human-machine interface (HMI).